Diagnosis, treatment and management of lipodystrophy: the physician perspective on the patient journey - Patni, Nivedita; Chard, Craig; Araújo-Vilar, David; Phillips, Helen; Magee, David A.; Akinci, Baris (Orphanet journal of rare diseases, 2024)
Background Lipodystrophy syndromes are a heterogeneous group of rare, life-limiting diseases characterized by a selective loss of adipose tissue and severe metabolic complications. There is a paucity of information describing the experiences and challenges faced by physicians who have seen and treated patients with lipodystrophy. This study aimed to provide a better understanding of the physician’s perspective regarding the patient journey in lipodystrophy, including diagnosis, the burden of disease, and treatment approaches. Methods Thirty-three physicians from six countries who had seen or treated patients with lipodystrophy were interviewed using a semi-structured questionnaire. Interviews were transcribed, anonymized, and analyzed for themes and trends. Four main themes were developed: (1) the diagnostic journey in lipodystrophy including the disease features or ‘triggers’ that result in the onward referral of patients to specialist medical centers with experience in managing lipodystrophy; (2) the impact of lipodystrophy on patient quality of life (QoL); (3) the use of standard therapies and leptin replacement therapy (metreleptin) in lipodystrophy, and (4) barriers to metreleptin use. Results Participants reported that, due to their rarity and phenotypic heterogeneity, lipodystrophy cases are frequently unrecognized, leading to delays in diagnosis and medical intervention. Early consultation with multidisciplinary specialist medical teams was recommended for suspected lipodystrophy cases. The development and progression of metabolic complications were identified as key triggers for the referral of patients to specialist centers for follow-up care. Participants emphasized the impact of lipodystrophy on patient QoL, including effects on mental health and self-image. Although participants routinely used standard medical therapies to treat specific metabolic complications associated with lipodystrophy, it was acknowledged that metreleptin was typically required in patients with congenital generalized lipodystrophy and in some acquired generalized and partial lipodystrophy cases. A lack of experience among some participants and restrictions to access remained as barriers to metreleptin use. Conclusions To our knowledge, this is one of the first studies describing the qualitative experiences of physicians regarding the diagnosis and management of lipodystrophy. Other physician-centered studies may help increase the awareness of lipodystrophy among the wider medical community and support clinical approaches to this rare disease.